Pelatihan Pola Penerapan Mekanisme Koping sebagai Upaya Meningkatkan Kesejahteraan Psikologis Ustadz/ Ustadzah di Kabupaten Banyuwangi - Yuli Fitria; Yulifah Salistia Budi; Fransiska Erna Damayanti (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
Perceptions of ustadz/ustadzah in Islamic boarding schools tend to have a spiritual level and form good character. However, this stigma can cause feelings of being required to always be wise, precise in managing problems that have an impact on psychological well-being. The purpose of this community service activity was to provide hard and soft skills in the form of applying adaptive coping mechanism patterns in dealing with problems. The method used training that includes psycho education awareness, habituation and practice. The results showed that there was an increase in knowledge and a significant positive effect on the ability to choose adaptive coping with partners. Based on the results and discussion, it can be concluded that the ability to choose adaptive coping mechanisms is the right and effective way to deal with problems and can improve psychological well-being.